On a Class of Bimodal Distributions and their Applications in Modelling Bimodal Error Data - Anjana V.; P. Yageen Thomas; Manoj Chacko (Journal of the Indian Society of Agricultural Statistics, 2025)
A new family of bimodal distributions is introduced in this paper with an objective of using them for modelling error data sets. A new class of statistics arising from a symmetric distribution is proved to have distributions belonging to the family of the bimodal distributions introduced in this work. The information matrix is derived after addressing the problem of obtaining maximum-likelihood estimates for the parameters of generalized bimodal distribution. A simulation study is conducted to evaluate the properties of maximum likelihood estimators. The applications of the results in building bimodal distributions for some real life data sets are also illustrated.